Lexicultura: construção desconstrução reconstrução da identidade do brasil(eiro) : entre projeções e planificações de projetos coloniais - Lopes, Lúcia Helena Ferreira (2016)
This paper focuses on the genesis of the establishment of the identity of the Brazilian people, perceived as a dynamic process explained by the knowledge stored in the long-term, medium-term and short-term memories by cultural, ideological and utopic assumptions. In this context, we focused on identity through a historiographical point of view, considering language as the basis and the ground of this process and considering the written text as a means that enables understanding and reinterpreting the language. The theoretical and methodological grounds that allowed developing the subject studied herein derived from the text/discourse-related linguistics within the social-cognitive-interactive branch, interfacing with those found in Lexicology, so as to enable the reading and re-reading of/in the gaps of the Brazilian official history by reading and re-reading the Chilean Letters. The results obtained, in line with the general goal – understanding the processes that led to the establishment of the identity of the Brazilian people through History texts that address the meanings described in two projects: one concerning the colonization of Brazil by the Portuguese people and another one concerning the political independence of the Brazilian colony – lead to the following conclusions: a) the narrative is a slow, gradual process, guided and organized by the creation or reinvention of ancient stories; a cultural production through which the event, past events or future events can be identified in the gaps of past: the basis for building utopias; b) the projections about the antipodes, part of the imagination of ancient people and represented as an island, preserved the representations inherited from mythology, religion and science, and, after the discovery of the fourth continent, they represented a mental work of reconstruction of the Earth‟s cartography; c) the discovery of America, including the finding of Island of the True Cross therein, on the one hand, served as proof of the projections imagined by the people, and, on the other hand, enabled the planning of the Portuguese project of expanding their lands beyond the borders of Old Europe; d) the Portuguese plans for the occupation, use and possession of colonized lands was guided by agreements and arrangements made in special with the indigenous people responsible for the strategies of dismantling tribes and the territories and the development of a significant informal market, which – with the cooperation of people from Guinea – financed, slowly and gradually, several colonial undertakings, including the discovery of goldmines: imagined projections. In this local context, multiracial people stand out, along with the plans of political and economic independence of the Colony from the high taxes levied by the Portuguese: foundations of the history narrative and also the literature of Brazil as a Colony. Considering this global context, one can conclude that the identity of Brazilian people is a process inserted in the history of native American people, influenced by the history of Eastern European people and Sub-Saharan Africans: the establishment of the history of the modern world as reinterpreted by the history of the ancient world